METHOD DEVELOPMENT AND VALIDATION FOR THE SIMULTANEOUS DETERMINATION OF METOPROLOL AND ATORVASTATIN BY REVERSED-PHASE HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY IN ITS BULK AND PHARMACEUTICAL TABLET DOSAGE FORM USING BIORELEVANT DISSOLUTION MEDIA (FASTED STATE SMALL INTESTINAL FLUID) - Shanmugasundaram, Palani; Sk2, Kamarapu (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: A present investigation is based on method development and validation for the simultaneous determination of metoprolol and atorvastatin by reversed-phase high-performance liquid chromatography in its bulk and pharmaceutical dosage form using a biorelevant dissolution media (fasted state small intestinal fluid). Methods: The chromatographic separation technique performed by an isocratic method for this column used Inertsil ODS-3 (4.6×150 mm, 5 μm). The ratio of mobile phase used is phosphate buffer 4.8 pH: acetonitrile (35:65v/v), flow rate 1 ml/min, and analysis time 15.0 min, UV detection was at 244 nm. Results: According to the International Conference on Harmonisation Q2 (R1) guidelines, the method validation was done. Peaks were observed at 2.227 min and 5.819 min, concentration range of linearity was obtained at 50–250 μg/ml and 10–50 μg/ml, linearity correlation coefficients were 0.9997 and 0.9995, limit of detection was 0.33 mg/ml and 0.21 mg/ml, and limit of quantification was 1.08 mg/ml and 0.69 mg/ml for metoprolol and atorvastatin, respectively. Conclusion: The obtained results for this method validation are within acceptance criteria. This method was more economical and stable for routine analysis.